The Implementation of Innovative Technology-Based Project Based Learning Models in Enchancing Student Creativity - Munir, Nur Syamsinar; Nooviar, Muh. Syilfa; Khairunnisa, Andi Anindita; Augustyn, Elisabeth Kristina (Universitas Negeri Makassar, 2023)
Abstract. This research aims to understand the implementation of the innovative technology-based project-based learning model in improving students' creativity and to determine the influence of the innovative technology-based project-based learning model on enhancing student creativity. The research method used in this study is a quantitative approach with a survey research design. The population size is 40 individuals, and a sample of 20 individuals was selected through random sampling. Data collection methods included observation, interviews, documentation, and questionnaires. Assumptions were tested for normality and linearity. Data analysis involved a simple linear regression test. The results of this research indicate that (1) The description of the implementation of the innovative technology-based project-based learning model falls into the